Sensitizing Emotional Intelligence: a blooming hope for Unforeseen Retinal Ailment - Rani, Kavitha; Revanth, R.; Shanmughavadivu, Dr.N.S.; Flower, Dr.F.X. Lovelina Little (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
Concerns regarding one's mental health that are not treated score highest among all diseases. Even though the world has made significant advancements in research and development and awareness of the impact of mental disorders is not properly recognised, developing countries still spend barely 2% of their health budgets on mental health services. This is despite the fact that anxiety and depression have increased by 25% during the last few years. In addition, the WHO reports that developing countries have spent barely any of their health budgets on mental health services. Emotional intelligence is necessary in order to sustain a relationship, boost job satisfaction, effectively handle the stress associated with kinfolk, and reframe adverse circumstances. Several studies point to the importance of emotional intelligence as a factor in the treatment of mental disorders. The emotional quotient (EQ), which is often commonly referred to as emotional intelligence, is the cutting edge of human intellect. It was much more challenging to overcome a mental ailment that had been brought on by a physical handicap. It can be quite challenging to cope with the inadvertent loss of eyesight caused by a retinal ailment, which can result in challenges on both a psychological and a financial level. The purpose of this research is to analyse the characteristics of emotional intelligence of early adults who have unexpected vision impairment owing to a retinal ailment by doing a critical review of previously published articles. In addition to that, the importance of psychosomatic ophthalmology is emphasised throughout this work.
Keywords: Mental health; Emotional Intelligence; Retinal Ailment; Psychosomatic Ophthalmology